Investigation into practical strategies for enhancing language development at billingual environment - Gulzat Urazova (Research Retrieval and Academic Letters, 2024)
This study explores the influence of teachers' linguistic and philological expertise on language acquisition and educational outcomes in early childhood, particularly focusing on English language development within a Kazakh-dominant environment in Kazakhstan. By examining the promotion of English among children aged 2-5 through interactive storytelling and play, the research underscores how heritage language development can be effectively nurtured in bilingual settings. The study also evaluates the challenges and successes of implementing language immersion programs in early education, stressing the importance of targeted professional development to empower teachers to leverage their linguistic strengths in creating inclusive, engaging learning environments. These findings aim to inform broader educational strategies that emphasize multilingualism and cultural inclusivity, advocating for systemic reforms that capitalize on educators' linguistic assets to enhance equity in early childhood education.